Gestão de negócios familiares: a busca pela profissionalização de uma empresa familiar do ramo de varejo de combustíveis - Lopes, Caroline Vitório (Universidade do Vale do Rio dos Sinos, 2015)
This paper aims to identify possible improvements in the management of a family business of fuel retailing industry seeking better structuring and professionalization of that company. Therefore, it is important to address issues such as the concept of family business approach and the tools used for professionalization and family governance. With the use of qualitative methodology, through a case study, a semi structured interview was carried out and later on the analysis of such data was performed in a descriptive manner. It is disclosed that the company, object of study of this paper, has the initial arrangements for the professionalization and an important step to evolve its informal to formal management is the implementation of the family council.
Keywords: Empresa familiar; Profissionalização; Governança; Varejo de combustíveis; Family business; Professionalization; Governance; Fuel retailing industry